Sexual life changes in pregnant women during COVID-19 outbreak - Eserdağ, Süleyman; Yücedağ, Mehtap; Anğın, Ali Doğukan; Yılmaz, Özgür; Ertekin, Lokman Tekin; Anğın, Pınar (Journal of Surgery and Medicine, 2021)
Background/Aim: Restrictions imposed after the COVID-19 outbreak have had some negative effects on the society and individuals. There are few reports on the effects of the COVID-19 pandemic, which causes stress on individuals, on sexual activity. The aim of this study is to evaluate the sexual activities of pregnant women during these restrictions. Methods: A total of 294 pregnant women between the ages of 18-45 years and their spouses who visited the Gynecology and Obstetrics Clinic between June 2020, and August 2020 were included in this cross-sectional study. The sexual activities of pregnant women and their spouses were evaluated with the Arizona Sexual Experiences Scale (ASEX). Results: One third of the pregnant women were in their first pregnancy, and 78.2% of those who gave birth before had a vaginal delivery. 38.8% of the pregnant women were in their second trimester. The mean ASEX scores of pregnant women and their partners during the pandemic period were significantly increased compared to the pre-pandemic period (13.47 (3.58) versus 17.01 (5.78), P=0.001, 12.14 (2.98) versus 14.49 (5.02), P=0.001, respectively). Before the pandemic, 64.62% (n=190) of the pregnant women and 51.7% (n=152) of their spouses had a sexual disorder. During the pandemic, this ratio increased in both genders and rose to 80.27% (n=136) in pregnant women and 63.60% (n=187) in their spouses. Conclusion: We observed an increase in sexual dysfunction in both pregnant women and their partners during the COVID-19 pandemic.